Winners and Losers in the European Monetary Union, A Neural Network Analysis of Spatial Industrial Shifts - Peter Nijkamp; Shunli Wang (Tinbergen Institute, 1998)
The forthcoming creation of a single European currency area will likely have farreaching impacts on the competitive position of European industries, as a result of a decline in transaction costs and currency risks for intra-European trade. These impacts will take place independent of the question whether the 15 EU countries form an Optimum Currency Area or not. The generally expected gains of trade from an integrated European market may therefore not be Pareto-optimal, as a monetary union may have significant distributional impacts on individual countries and regions. Then there will be winners and losers.This paper addresses the welfare impacts of a single European currency area by investigating industrial changes and shifts in location that may take place after the introduction of the EURO, based on the idea that fixed exchange rated in the EMU will be reflected in a decline in transportation costs and industrial clustering. The empirical analysis uses an extensive data set onindustrial production, interest rates and exchange rates in the various European countries.Two policy scenarios are envisaged, with a retrospective (backcasting)scenario on the likely effects ofa fixed exchange rate in the past anda fixed exchange linkage with the US dollar.Next, a neural network analysis is developed to trace for the two above mentioned scenarios the foreseeable and likely welfare effects of a single monetary union. It is concluded that the introduction of the EMU- according to the two past scenarios - would have worsened for most European countries the industrial competitiveness.
Keywords: 330; Währungsunion; Standortwettbewerb; EU-Staaten